La contabilidad en la Colonia (2012)
This paper aims at reflecting on the importance of accountability in the decisions made on a daily basis in different organizations based on historical facts, regardless of the period, and on the misuse of accountability. Using accountability correctly, honestly and professionally may generate more benefits than evil to society.